2014
DOI: 10.1073/pnas.1319001111
|View full text |Cite
|
Sign up to set email alerts
|

Superwetting of TiO 2 by light-induced water-layer growth via delocalized surface electrons

Abstract: Titania, which exhibits superwetting under light illumination, has been widely used as an ideal material for environmental solution such as self-cleaning, water-air purification, and antifogging. There have been various studies to understand such superhydrophilic conversion. The origin of superwetting has not been clarified in a unified mechanism yet, which requires direct experimental investigation of the dynamic processes of water-layer growth. We report in situ measurements of the growth rate and height of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 39 publications
3
31
0
Order By: Relevance
“…This friction reduction is attributed to the existence of the ordered water structures on the superhydrophilic surface with appropriate charge patterns, and the friction between this ordered water monolayer and the water molecules above is small. In practical applications, the ordered water monolayers have been observed on several real solid surfaces, 27,[36][37][38][39][40][41]44 suggesting that there is a high probability that materials associated with unique friction properties existing. Figure 1A, we have implemented the nonequilibrium Couette flow to investigate the surface friction based on molecular dynamics simulations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This friction reduction is attributed to the existence of the ordered water structures on the superhydrophilic surface with appropriate charge patterns, and the friction between this ordered water monolayer and the water molecules above is small. In practical applications, the ordered water monolayers have been observed on several real solid surfaces, 27,[36][37][38][39][40][41]44 suggesting that there is a high probability that materials associated with unique friction properties existing. Figure 1A, we have implemented the nonequilibrium Couette flow to investigate the surface friction based on molecular dynamics simulations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The interaction between water and oxides is important to control function in many technological applications, including water splitting 1,2,3,4,5,6,7 , rechargeable metal-air batteries 8,9,10,11,12 , surface wetting and self-cleaning 13,14,15,16 , photocatalysis 15,17,18,19,20 , sensors 15 , and proton-conducting oxide membranes 21,22,23,24 . Recent studies have shown that decreasing coverage of hydroxyl groups on a perovskite oxide surface at the water/oxide interface not only reduces wetting and but also enhances oxygen reduction kinetics in a basic solution 14 atom and hydroxyl group in the lattice oxygen site, respectively).…”
mentioning
confidence: 99%
“…water layer, which is attributed to the ''water wets water'' mechanism, affected the application of TiO2 film in a dark or non-UV environment [21,22]. Surface-engineered silica materials (SESMs) possessing surface activity successfully removed organic pollutants and bacteria from water [23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%